2007
DOI: 10.1103/physrevd.75.085012
|View full text |Cite
|
Sign up to set email alerts
|

Gluonic phases, vector condensates, and exotic hadrons in dense QCD

Abstract: We study the dynamics in phases with vector condensates of gluons (gluonic phases) in dense two-flavor quark matter. These phases yield an example of dynamics in which the Higgs mechanism is provided by condensates of gauge (or gauge plus scalar) fields. Because vacuum expectation values of spatial components of vector fields break the rotational symmetry, it is natural to have a spontaneous breakdown both of external and internal symmetries in this case. In particular, by using the Ginzburg-Landau approach, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 88 publications
0
62
0
Order By: Relevance
“…These include; (i) exploring a possibility of the mixed phase [15] along the line suggested earlier [54][55][56], (ii) the baryon current generation [16], (iii) examining the crystalline pairing phases [57] taking the neutrality constraints into account [17,18], (iv) investigating a possible secondary gap formation [19], (v) the gluon condensation in the g2SC [20], and (vi) an inhomogeneous (p-wave) Kaon condensate [21]. Examining all these possibilities or searching for a more stable ground state as well as exploring a nature of the gluonic instability in the gapless phases is now one of central problems in QCD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include; (i) exploring a possibility of the mixed phase [15] along the line suggested earlier [54][55][56], (ii) the baryon current generation [16], (iii) examining the crystalline pairing phases [57] taking the neutrality constraints into account [17,18], (iv) investigating a possible secondary gap formation [19], (v) the gluon condensation in the g2SC [20], and (vi) an inhomogeneous (p-wave) Kaon condensate [21]. Examining all these possibilities or searching for a more stable ground state as well as exploring a nature of the gluonic instability in the gapless phases is now one of central problems in QCD.…”
Section: Discussionmentioning
confidence: 99%
“…(20) and some matrix elements in these bases [36] without recourse to numerical derivatives done in [11,23,29]. The charge neutrality constraints can be also expressed in terms of the matrix elements in the basis composed of these eigen-spinors.…”
Section: B Representation Of Gap Equation and Kinetic Constraints Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that this type of instability is related to the local phase fluctuation of the superconducting order parameter, i.e., the Nambu-Goldstone boson fields [9,10,11,12]. This type of instability induces the formation of the single-planewave FF-like state [13,14,15,16,17].…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that this type of instability is related to the local phase fluctuation of the superconducting order parameter, i.e., the Nambu-Goldstone boson fields [9,10,11,12]. This type of instability induces the formation of the single-planewave FF-like state [13,14,15,16,17].The imbalanced cold atom systems such as the 40 K and 6 Li offer an intriguing experimental opportunity to understand the pair breaking states. However, recent experiments [18] on these systems did not show explicit evidence of the BP state or the LOFF state, rather they produced strong evidence of the phase separation at moderate mismatch.…”
mentioning
confidence: 99%